Politics and the Stock Market: Evidence from Germany - Christian Pierdzioch; Jörg Döpke (Kiel Institute for World Economics (IfW), 2004)
We analyze the interaction of stock market movements and politics in Germany. In contrast to the empirical evidence available for the U.S., we do not find that German stock market returns tend to be higher during liberal than during conservative governments. Also in contrast to results for the U.S., we find no evidence for an election cycle in German stock market returns. However, estimated popularity functions and VARs suggest that stock market returns have had an impact on the popularity of German governments. We find that this result is robust across different VAR specifications and time periods.
Keywords: E44; E32; G12; 330; Political business cycle; Stock market; Germany; Börsenkurs; Kapitalertrag; Politischer Konjunkturzyklus; Schätzung; Deutschland